Screening plants of the lle-Вalkhash region to the presence of the antiviral propertiesю (Eurasian Journal of Ecology, 2016)
A rich variety of flora Ile-Balkhash region can expect to the presence of a wide range biologically active compounds of plants. This paper presents a screening for antiviral activity of 15 herbal preparations isolatedfrom various environmental groups. It is shown that preparations IB2, IB12, IB13, IB15 from meso-, xeromeso and xerophytes in dose 1 mg per kg were able to inhibit virus replication by more than 75%. It was found thatthe virucidal activity of preparations IB13, IB15 and IB2 comparable to commercial preparations geviran and amizon and preparation IB12 is comparable for virucidal activity with commercial preparations based onalcohol-containing solutions.
Keywords: antiviral activity; virucidal activity; herbal preparations; phytocomplex influenza virus